Cover Feature: The Photocatalyzed Thiol‐ene reaction: A New Tag to Yield Fast, Selective and reversible Paramagnetic Tagging of Proteins (ChemPhysChem 9/2020). Issue 9 (6th May 2020) - Denis, Maxime; Softley, Charlotte; Giuntini, Stefano; Gentili, Matteo; Ravera, Enrico; Parigi, Giacomo; Fragai, Marco; Popowicz, Grzegorz; Sattler, Michael; Luchinat, Claudio; Cerofolini, Linda; Nativi, Cristina
Abstract : The Cover Feature illustrates the photo‐initialization by UV light of the thiol‐ene reaction between the alkene of a newly designed paramagnetic tag and the thiol group of the cysteine residue on a model protein. The protein tagging occurs in 1 hour. We tagged the protein with three different lanthanide ions, which induced different chemical shifts on the protein NMR signals. Paramagnetic restraints were measured and the tensor calculated. More information can be found in the Article by L. Cerofolini, C. Nativi and co‐workers .